2022
DOI: 10.3389/fnhum.2022.805452
|View full text |Cite
|
Sign up to set email alerts
|

Design of an Isometric End-Point Force Control Task for Electromyography Normalization and Muscle Synergy Extraction From the Upper Limb Without Maximum Voluntary Contraction

Abstract: Muscle synergy analysis via surface electromyography (EMG) is useful to study muscle coordination in motor learning, clinical diagnosis, and neurorehabilitation. However, current methods to extract muscle synergies in the upper limb suffer from two major issues. First, the necessary normalization of EMG signals is performed via maximum voluntary contraction (MVC), which requires maximal isometric force production in each muscle. However, some individuals with motor impairments have difficulties producing maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…In addition, PCA relies on signal normalization, which for EMG is performed via maximum voluntary contraction (MVC) of each muscle. However, this process is unreliable and true maximal force is difficult to attain in individuals with motor deficits (22). Here, we normalized EMG signals based on the maximal activity of each muscle during the gait cycle.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PCA relies on signal normalization, which for EMG is performed via maximum voluntary contraction (MVC) of each muscle. However, this process is unreliable and true maximal force is difficult to attain in individuals with motor deficits (22). Here, we normalized EMG signals based on the maximal activity of each muscle during the gait cycle.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that tasks involving the generation isometric multidirectional force can be used for extracting synergies (Borzelli et al 2013 ; Berger et al 2013 ; Gentner et al 2013 ; Barradas et al 2020 ; Borish et al 2021 ; Cho et al 2022 ). Therefore, the aim of the study was to investigate muscle synergies while maintaining and controlling the CoP fluctuations during upright standing posture in which participants were instructed to generate isometric forces to counteract small loads pulling in multiple directions.…”
Section: Introductionmentioning
confidence: 99%